Compositional Variation of Amphiboles During Magma Mixing: A Case Study of Huangyangshan A-Type Granite in Kalamaili Metallogenic Belt, East Junggar, China - Ye, Chenyang; Feng, Yonggang; Lei, Ruxiong; Yang, Gaoxue (Frontiers in Earth Science, 2021)
The Huangyangshan A-type granitic pluton is distributed along the thrust fault in the Kalamaili region of East Junggar, Xinjiang, China. The pluton is lithologically dominated by alkaline granite containing abundant dioritic enclaves that formed via magma mixing. Both the host granite and the enclaves contain calcic to sodic amphiboles. We determined major and trace element contents of amphiboles from both units. The results show that halogens and Mg are mainly controlled by chemical compositions of the magma and that Ti, Fe, and Al are sensitive to paragenesis of other minerals. By contrast, K, Na, and Ca concentrations in the amphiboles are likely influenced by crystal chemistry, rate of incorporation or diffusivity, and paragenesis of other minerals. Trace elements including HFSE and REE behave more compatibly in sodic amphibole than in calcic amphibole. Due to lack of applicable thermometer and barometer for sodic amphiboles, we can only tentatively estimate the crystallization temperature and pressure. Temperatures calculated using mineral composition-based thermometers and partition coefficient-based thermometers show considerable deviation. Amphibole-only thermometers, however, give more reasonable results that are consistent with petrographic evidence. All the currently available amphibole-based barometers rely on Al content or DAl and cannot be applied to Fe-rich and Al-poor amphiboles. Therefore, further studies on amphibole-based thermometers and barometers are needed.